Can high-volume teams of anesthesiologists and surgeons decrease perioperative costs for pancreatic surgery?. Issue 5 (May 2019) - Uppal, Abhineet; Vuong, Brooke; Dehal, Ahmed; Stern, Stacey L.; Mejia, Juan; Weerasinghe, Roshanthi; Kapoor, Vandana; Ong, Evan; Hansen, Paul D.; Bilchik, Anton J.
Abstract: Background: Pancreatic surgery outcomes are associated with surgeon and center experience. Anesthesiologists as potential value drivers for pancreatic surgery have not been explored. We sought to evaluate whether anesthesiologists impact perioperative costs for pancreatic surgery. Methods: Within an integrated health care system, 796 pancreatic surgeries (526 PDs and 270 DPs) were performed from January 2014 to June 2017. Mean direct operative and anesthesia costs driven by anesthesiologists (operating room (OR) time, anesthesia billing and anesthesia procedures) were determined for each case. The volumes of pancreatic cases per anesthesiologist were calculated, and those above the 75th percentile for volume (4 cases) were considered high-volume. A multivariable analysis of OR/anesthesia costs was performed. Results: Mean OR and anesthesia costs for PD were 7064 for low-volume anesthesiologists (LVA), higher than 5968 for high-volume anesthesiologists (HVA) (p < 0.001). By multivariable analysis, HVA were associated with decreased costs of 2278 (p < 0.001). Teams of HVA and high-volume surgeons (HVS) were also associated with decreased mean costs of 1790 (p = 0.04). Conclusion: These data suggest that anesthesiologists experienced in the management of complex pancreatic operations such as PDs may contribute to improved efficiencies in care by reducing perioperative costs.